Humoral immunity in natural infection by tick-borne encephalitis virus - Venturi, Giulietta; Martelli, Paola; Mazzolini, Elena; Fiorentini, Cristiano; Benedetti, Eleonora; Todone, Daniele; Villalta, Danilo; Fortuna, Claudia; Marchi, Antonella; Minelli, Giada; Ciufolini, Maria Grazia (Journal of medical virology, 2009)
Tick-borne encephalitis (TBE) virus is one of the most important flaviviruses associated with neurological disease in Europe. Cross-reactive antibodies elicited by different flaviviruses can make difficult the interpretation of ELISA and hemagglutination-inhibition (HI) tests for the diagnosis of TBE. Neutralization tests, which are more specific, are not in common use because they are difficult to perform and standardize. A plaque reduction neutralization test (PRNT), optimized previously in vaccinated children, was evaluated in sera from acute cases of TBE, collected for diagnostic purposes, and from healthy human population and wild ruminants, collected for serosurvey purposes. The PRNT results were compared with the results of ELISA and HI tests. In acute TBE disease, most sera were positive for IgM antibodies by ELISA and with high HI antibody titers; neutralizing antibodies were detected in 71.4% of patients, at a very low titer (1:10 NT₅₀) in almost all cases. Seroprevalences of 8% and 6.5% for anti-TBE ELISA antibodies were found in healthy subjects and wild ruminants, respectively. Among anti-TBE positive healthy subjects, a very low 1:10 NT₅₀ titer was detected in 17.4% of cases, while NT₈₀ titers ranging from 1:10 to 1:80 were detected in 65.2% of cases. Among wild ruminants, 90.9% of ELISA and HI positive samples showed a positive, greater-than-or-equal1:10 NT₈₀ titer. In conclusion, neutralization assays can be useful for the diagnosis and serosurveys of TBE. J. Med. Virol. 81:665-671, 2009